Burden of gout in the Nordic region, 1990–2015: findings from the Global Burden of Disease Study 2015. (3rd September 2018) - Kiadaliri, AA; Uhlig, T; Englund, M
Abstract : Objective : To explore the burden of gout in the Nordic region, with a population around 27 million in 2015 distributed across six countries. Method : We used the findings of the 2015 Global Burden of Diseases study to report prevalence and disability associated with gout in the Nordic region. Results : From 1990 to 2015, the number of prevalent gout cases rose by 30% to 252 967 [95% uncertainty interval (UI) 223 478‒287 288] in the Nordic region. In 2015, gout contributed to 7982 (95% UI 5431‒10 800) years lived with disability (YLDs) in the region, an increase of 29% (95% UI 24‒35%) from 1990. While the crude YLD rate of gout increased by 12.9% (95% UI 7.8‒18.1%) between 1990 and 2015, the age-standardized YLD rate remained stable. Gout was ranked as the 63rd leading cause of total YLDs in the region in 2015, with the highest rank in men aged 55–59 years (38th leading cause of YLDs). The corresponding rank at the global level was 94. Of 195 countries studied, four Nordic countries [Greenland (2nd), Iceland (12th), Finland (14th), and Sweden (15th)] were among the top 15 countries with the highest age-standardized YLD rate of gout. Conclusion : The burden of gout is rising in the Nordic region. Gout's contribution to the total burden of diseases in the region is more significant than the global average. Expected increases in gout burden owing to population growth and ageing call for stronger preventive and therapeutic strategies for gout management in Nordic countries.